Targeting STEAP1 as an anticancer strategy - Nakamura, Hajime; Arihara, Yohei; Takada, Kohichi (Frontiers in Oncology, 2023)
Although the six-transmembrane epithelial antigen of prostate 1 (STEAP1) was first identified in advanced prostate cancer, its overexpression is recognized in multiple types of cancer and associated with a poor prognosis. STEAP1 is now drawing attention as a promising therapeutic target because of its tumor specificity and membrane-bound localization. The clinical efficacy of an antibody-drug conjugate targeting STEAP1 in metastatic, castration-resistant, prostate cancer was demonstrated in a phase 1 trial. Furthermore, growing evidence suggests that STEAP1 is an attractive target for immunotherapies such as chimeric antigen receptor-T cell therapy. In this review, we summarize the oncogenic functions of STEAP1 by cancer type. This review also provides new insights into the development of new anticancer strategies targeting STEAP1.